The crystal growth of NASICON phase from the lithium germanium phosphate glass - Matijašević Srđan D.; Topalović Vladimir S.; Savić Veljko V.; Labus Nebojša J.; Nikolić Jelena D.; Zildžović Snežana N.; Grujić Snežana R. (Science of Sintering, 2023)
The crystal growth rate of LiGe2(PO4)3 phase from lithium germanium-phosphate glass was studied. The glass have been homogenized using the previously established temperature-time conditions, which make it possible to remove volatile substances from the glass melt. The atomic absorption spectrophotometry (AAS) was used to determine the chemical content of the obtained glass and scanning electron microscope (SEM) were used to reveal the isothermal process of crystal growth. The crystal growth rates were determined experimentally and theoretically.